Odpowiedzi

Najlepsza Odpowiedź!
2010-02-15T21:48:15+01:00
A) x+2y=-2
2x-y=1

x=-2-2y
2*(-2-2y)-y=1

x=-2-2y
-4-4y-y=1

x=-2-2y
-5y=5/:(-5)

x=-2-2y
y=-1

x=-2-2*(-1)
y=-1

x=0
y=-1

b) x+4y=-2
3x-8y=10

x=-2-4y
3*(-2-4y)-8y=10

x=-2-4y
-6-12y-8y=10

x=-2-4y
-20y=16 /:-20

x=-2-4y
y= -4/5

x=-2-4*(-4/5)
y=-4/5

x=-1 i 1/5
y=-4/5

c) x-2y=3
-2x+4y=0 / :2

x-2y=3
-x+2y=0
__________
0 nie= 3

równanie sprzeczne

d) 2x+y=9
5x-4y=3

y=9-2x
5x-4(9-2x)=3

y=9-2x
5x-36+8x=3

y=9-2x
13x=39 /:13

y=9-2x
x=3

y=9-2*3
x=3

y=3
x=3

e) 3x-2y=5
2x-y=4

3x-2y=5
-y=4-2x /*(-1)

3x-2y=5
y=-4+2x

3x-2(-4+2x)=5
y=-4+2x

3x+8-4x=5
y=-4+2x

-x=-3
y=-4+2x

x=3
y=-4+2*3

x=3
y=2